Effects of impeller trim on performance of two-stage self-priming centrifugal pump. (February 2017) - Wang, Kai; Zhang, Zixu; Jiang, Linglin; Liu, Houlin; Li, Yu
In order to save energy by broadening its application range, the influence of impeller trim on the performance of a two-stage self-priming centrifugal pump was numerically studied. The hydraulic performance experiments and self-priming experiments were carried out. And the unsteady performance of pressure fluctuation and radial force in the pump was analyzed. The results show that with the increase in impeller trim quantity, the best efficiency point of the pump would move to the small flow rate condition. Under the design flow rate, when both the two stages of the impeller were trimmed by 6%, head of the pump was reduced by 13%, efficiency of the pump was as well decreased by 1.69 percentage points, and self-priming time was increased by 1.7%. Thus, impeller trim can be used to meet the operating requirements in the head range of 94–107 m. With the increase in impellers trim quantity, the pressure fluctuation in the positive channel of the radial guide vane and the volute was smaller, while the radial force on the wall of radial guide vane and volute was also smaller.